Hubungan Pemberian ASI Dini dengan Kejadian Ikterus Bayi Baru Lahir di Klinik Pratama Serasi Tahun 2022 - Suci Adfila Nofenna; Safitri Handayani; Srininta Srininta; Rahmaini Fitri Harahap (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Epidemiological Data indicate that more than 50% of newborns suffer from jaundice in the first week of life. Physiological jaundice arises on the second and third days, which is characterized by jaundice coloring of the skin and sclera due to the accumulation of excess and unconjugated bilirubin. The study aims to determine the relationship of maternal characteristics (gestational age, parity, type of Delivery), Infant characteristics (infant birth weight), how to cope with the incidence of maternal jaundice newborns.This type of research is descriptive research with cross sectional design approach. The population in this study all postpartum mothers who gave birth in the clinic and who were referred to the hospital during March s/D July as many as 40 people, a large sample of 36 people. Purposive sampling technique. Data analysis using univariate and bivariate. Chi square test results are known to have a relationship of gestational age (p-value 0.015 < 0.05), parity (p-value 0.003 < 0.05), type of delivery (p-value 0.016 < 0.05), birth weight (p-value 0.018 < 0.05), how to handle postpartum mothers (p = 0.009 < 0.05) with the incidence of newborn jaundice.It is expected that postpartum mothers know the benefits of breastfeeding from an early age and maintain nutrition during breastfeeding to meet the needs of breast milk in infants so as to reduce the risk of jaundice.